2004
DOI: 10.1094/pdis.2004.88.9.989
|View full text |Cite
|
Sign up to set email alerts
|

Pearl Millet for the Management of Pratylenchus penetrans in Flue-Cured Tobacco in Quebec

Abstract: Two 1-year rotation experiments were conducted from 1998 to 2000 to assess the impact of forage and grain pearl millet (Pennisetum glaucum) on Pratylenchus penetrans populations in a tobacco field (Nicotiana tabacum cv. Delgold) in Quebec. Performance of these crops was compared with rye, the standard rotation crop. Rye plots were doubled to include a fumigated standard (application of metham sodium at 67.4 liters/ha on a band). Forage pearl millet increased tobacco yields by an average of 103% compared with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…In contrast, our results support previous studies which demonstrated that grain pearl millet is a poor host of P. penetrans when compared with rye (Bélair et al 2004;Jagdale et al 2000).…”
Section: Resultssupporting
confidence: 91%
“…In contrast, our results support previous studies which demonstrated that grain pearl millet is a poor host of P. penetrans when compared with rye (Bélair et al 2004;Jagdale et al 2000).…”
Section: Resultssupporting
confidence: 91%
“…A study by Jagdale et al (2000) reported no effect on tobacco yield due to millet rotation, compared with the winter rye fumigated or non-fumigated control plots. Bélair et al (2004) observed that tobacco yields in plots previously planted to forage millet or grain millet were significantly higher than those of the rye non-fumigated control, and were similar to those of the rye-fumigated plots. Ball-Coelho et al (2003) and more recently Bélair et al (2005), who used potato as the associated crop, reported similar results.…”
mentioning
confidence: 56%
“…In addition, comparisons based on the non-fumigated winter rye plots show a yield increase of 19 to 70% in tobacco following forage millet, tobacco following grain millet had a yield increase of 18 to 65% and tobacco following winter rye with fumigation showed a yield increase of 14 to 51%. Bélair et al (2004) working with forage millet var. CFPM 101 and grain millet vars.…”
Section: Pratylenchus Pentrans Populations In the Year Of Tobacco Promentioning
confidence: 99%
See 1 more Smart Citation
“…Stekh. ] when grown in rotation with susceptible crops (BallCoelho et al 2003;Be´lair et al 2004Be´lair et al , 2005Be´lair et al , 2006. Hybrids of grain pearl millet adapted to eastern Canadian conditions are dwarf and early maturing (100 d).…”
mentioning
confidence: 99%